Alih Fungsi Seni dalam Masyarakat Kompleks: Kasus Liang-Liong dan Barongsai - Yasmine Zaki Shahab (Antropologi Indonesia, 2000)
Betawi culture is filled with traditions rooted in the myriad ethnic groups that came together to form that culture in the past. Some of these traditions have on occasion been the subject of debate as to their proper origin. While some traditions have disappeared, those that are of Chinese origin have been repressed or outlawed during the past several decades. However, the author notes that since the fall of the New Order in Indonesia, performances of the Liangliong and Barongsai have been staged ever more frequently. She discussed the problem within the framework of Hobsbawm's 'invention of tradition', and goes to show how there invention of these performances is marked by a change in their functions, and is linked to a previously unacknowledged Betawi elite.